Sosialisasi Hubungan Industrial, Jaminan Sosial, dan Komunikasi Efektif sebagai Persiapan Kerja Bagi Siswa SMK Negeri 20 Jakarta - Utami, Yeski Putri; Sari , Mudiana Permata; Djohan, Henry Anggoro (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Community Service Activities (PKM) carried out at SMK Negeri 20 Jakarta aim to improve students' knowledge and skills in facing the world of work, especially in aspects of industrial relations, social security, and workplace communication. Through a practice-based learning approach, namely an interactive and applied teaching-learning approach that is not only theoretical, but students are asked to directly practice and demonstrate industrial relations activities related to employment relations, social security, and effective communication. The activity was carried out for one day with a total of 100 participants. The evaluation method used was pretest-posttest to obtain quantitative data to measure the increase in participants' knowledge before and after the PKM activity. The obstacles and barriers faced in the field included low initial knowledge levels, lack of participant interest in employment topics, and limited implementation time. However, the results of data calculation and participant participation from start to finish showed that the PKM activity succeeded in making a positive impact on knowledge and increasing participant interest related to employment knowledge, especially employment relations, social security, and communication skills that can be used to face the world of work.